Upaya Peningkatan Produksi Kacang Hijau (Phaseolus radiatus L.) Melalui Pemberian Pupuk Hayati dan NPK - ., Suherman; Kiswondo, Sumiarjo; Hamdani, Muh. (Program Studi Agroteknologi, 2024)
Mung beans (Phaseolus radiatus L.) were one of the agricultural commodities that have very good prospects for development in Indonesia. Mung beans were the third most important legume commodity after soybeans and green beans. In Indonesia, green bean productivity was still low and cultivation land was limited to marginal land with a productivity of 1.1 tonnes per hectare and a potential yield of 2 tonnes per hectare (BPS, 2019). Causing factors the decline in green bean production include low soil fertility, land conversion, climate factors and cultivation factors. Efforts to increase production were by increasing soil fertility by providing complete fertilizer (NPK) and adding biological fertilizer. So it is necessary to carry out research to increase growth and production of green beans with balanced NPK fertilizer and biological fertilizer. The aim of this research was to determine the application of biological fertilizer to the growth and production of mung bean plants, to determine the application of NPK fertilizer to the growth and production of mung bean plants, to determine the interaction between biological fertilizer and NPK fertilizer on the growth and yield of mung bean plants. The research was conducted in Paleran Village, Umbulsari District, Jember Regency. The research was carried out using a Randomized Block Factorial Design (RAKF) consisting of 2 factors with 3 replications. The data obtained were analyzed of varians followed by Duncan's 5% average test. The conclusion of this research was that biological fertilizer (C2) treatment with a concentration of 5 liters per hectare has an effect on the growth and production of mung beans, NPK (P3) fertilizer treatment with a dose of 400 kg per hectare has an effect on the growth and production of mung beans, there was an interaction between biological fertilizers 5 liters per hectare with 400 kg NPK fertilizer per hectare (C2P3) on mung bean production variables. It was recommended that the results of this research be used as recommendations for mung bean farmers to increase production on marginal land.